Composite connections between CFS beams and plywood panels for flooring systems: Testing and analysis. (June 2022) - Karki, Dheeraj; Al-Hunaity, Suleiman; Far, Harry; Saleh, Ali
Abstract: A composite floor consisting of cold-formed steel (CFS) beams connected to structural plywood panels is a sustainable and economical alternative to concrete only floors or the traditional floor systems supported by solid lumber joists. The structural performance of the composite CFS-plywood floor depends on the strength and stiffness properties of the shear connection. This study presents an experimental investigation into the load-slip behaviour of connections between CFS and plywood panels constructed with self-drilling screws, coach screws, and nut and bolt. The influence of structural adhesives at the shear interface alongside fasteners was also investigated. The stiffness, ductility and load-carrying capacity of the eight different types of connections were evaluated through a series of push-out tests. Nut and bolt connections were demonstrated to be the best choice amongst the shear connectors, followed by self-drilling screws; however, the size of the nuts and bolts should be determined based on the crushing strength of the timber itself. Connection with coach screws was less stiff and relatively less ductile than other tested shear connections. Composite connections with fasteners along with adhesives demonstrated higher stiffness and load-capacity than the fastener alone. Furthermore, a simple analytical expression for the load-slip response of the connections is proposed based on the Foschi formula, which showed a good correlation with test results. Based on the observations in this study, self-drilling screws and M8 nuts and bolts are recommended as shear connectors for lightweight cold-formed steel and timber flooring systems.